Ammonia metabolism in chronic obstructive pulmonary disease with special reference to congestive right ventricular failure. Issue 6 (November 1974) - Valero, A.; Alroy, G.; Eisenkraft, B.; Itskovitch, J.
Abstract : Valero, A., Alroy, G., Eisenkraft, B., and Itskovitch, J. (1974). Thorax, 29, 703-709. Ammonia metabolism in chronic obstructive pulmonary disease with special reference to congestive right ventricular failure. A study of 36 patients was undertaken to evaluate the role of raised blood and CSF ammonia in the production of central nervous manifestations in chronic obstructive pulmonary disease (COPD) with special reference to congestive right ventricular failure (CRVF). The patient material comprised five categories: 11 controls, seven mentally alert patients with COPD, eight with COPD and CRVF, four with primary cardiac disease and CRVF, and eight with cirrhosis of the liver. Each patient was examined clinically especially for neurological manifestations such as asterixis, confusion, and drowsiness. Each patient also had measurement of venous pressure, bromsulphthalein, ECG, chest radiograph, and spirometry. The mean values of CSF-glutamine, CSF and arterial blood-ammonia, pH, P co 2, and P o 2 for each group were compared and statistically analysed. The results indicate that no correlation existed between central nervous manifestations acid-base balance or P o 2 . Ammonia-glutamine levels were found to relate to hepatic congestion whether it was caused by primary cardiac or pulmonary heart disease.